The microbiota-gut-brain axis: clinical applications in obesity and type 2 diabetes - Brandy Moser; Megan A. Milligan; Maria C. Dao (Permanyer, 2022)
Recent investigations highlight the importance of the gut microbiota and bacteria-derived metabolites as key components in obesity and metabolic health. The microbiota-gut-brain axis presents promising targets for future obesity treatments and prevention. However, the current state of evidence and existing clinical applications of the microbiota-gut-brain axis have yet to be summarized in a thorough review. Therefore, we sought to examine current evidence on the effect of lifestyle, dietary, pharmacological, and surgical interventions on the microbiota-gut-brain axis. In addition, this review highlights potential next steps in research toward characterizing the role of the microbiota-gut-brain axis in metabolic health, along with possible interventions to address obesity.